2020
DOI: 10.1093/bib/bbaa342
|View full text |Cite
|
Sign up to set email alerts
|

Dppa2/4 as a trigger of signaling pathways to promote zygote genome activation by binding to CG-rich region

Abstract: Developmental pluripotency-associated 2 (Dppa2) and developmental pluripotency-associated 4 (Dppa4) as positive drivers were helpful for transcriptional regulation of zygotic genome activation (ZGA). Here, we systematically assessed the cooperative interplay of Dppa2 and Dppa4 in regulating cell pluripotency and found that simultaneous overexpression of Dppa2/4 can make induced pluripotent stem cells closer to embryonic stem cells (ESCs). Compared with other pluripotency transcription factors, Dppa2/4 can regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Another marker, DPPA2 , acts as the main activator of the ZGA transcription program by directly regulating the mouse ZGA transcription factor Dux ( 53 ). DPPA2 contributes to the transcriptional regulation of ZGA in humans and mice and is significantly activated in mouse 2-cell embryos and 4–8-cell embryos ( 54 ). Our study indicated that DPPA2 is highly expressed at the 4-cell stage and continues to be highly expressed at the 8-cell and morula stages.…”
Section: Discussionmentioning
confidence: 99%
“…Another marker, DPPA2 , acts as the main activator of the ZGA transcription program by directly regulating the mouse ZGA transcription factor Dux ( 53 ). DPPA2 contributes to the transcriptional regulation of ZGA in humans and mice and is significantly activated in mouse 2-cell embryos and 4–8-cell embryos ( 54 ). Our study indicated that DPPA2 is highly expressed at the 4-cell stage and continues to be highly expressed at the 8-cell and morula stages.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression analysis was performed by R package DEseq2 [ 53 ]. For each comparison, genes with a Benjamini and Hochberg-adjusted p -value (false discovery rate, FDR) < 0.05 and the absolute of Log2 (fold change) > 1 were regarded as differential expression genes (DEGs) [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…KEGG database 4 : KEGG was established in 1995 by the Kanehisa Laboratories at the Bioinformatics Center, Kyoto University, Japan, and is now one of the most commonly used international bioinformatics databases ( Kanehisa and Goto, 2000 ). KEGG is a database used to understand the high-level functions and practicability of biological systems from molecular-level information ( Li H. et al, 2020 ; Wang et al, 2021a ) (especially large-scale molecular datasets generated by genome sequencing and other high-throughput techniques), of which the data information can be roughly classified into four major categories: system information, genetic information, chemical information, and medical information.…”
Section: Three Factorsmentioning
confidence: 99%